S-parameters of bismuth iron garnet (BIG) filled polyvinylidene fluoride composite using rectangular waveguide method - Soleimani, H. (Trans Tech Publications Ltd, 2014)
Nanosized Bismuth Iron Garnet (BIG) was synthesized via sol-gel method. The nanomaterials with ferrite structure were heat-treated at different temperatures from 700 to 1100 Â°C. The structure and morphology were characterized by Powder X-ray diffraction (PXRD). The PXRD show that with the increase of temperature the size of crystallites for BIG gradually increased. The BIG ferrite nanopowder was composited with polyvinylidene fluoride (PVDF) by solution casting method with different ferrite ratios. The magnitudes of S-parameters of PVDF/BIG were investigated using rectangular waveguide in conjunction with a microwave vector network analyzer (VNA) at microwave frequencies. The S-parameters of PVDF/BIG are found to be slightly different from those of ferrite contents in polymer composites. The S11 is found to be increased by increasing the ferrite content of the composites as well as with frequency while the S21 is observed to decrease with increase in ferrite content. Â© (2014) Trans Tech Publications, Switzerland.